The Phenomenon of Learning Motivation of Elementary School Students - Edu, Ambros Leonangung; Jaya, Petrus Redy P.; Ni, Laurentius (Universitas Pendidikan Ganesha, 2021)
Learning motivation is one of the important things that can affect the student's learning process. This study aims to explore the phenomenon of learning motivation of elementary school students. This research is quantitative research using survey exploratory research. Subjects involved in this study amounted to 51 elementary school students. Data collection uses a questionnaire as a data collection instrument. The questionnaire was compiled based on four components of learning motivation, namely the drive for achievement, discipline in learning, readiness to overcome difficulties, and curiosity. The questionnaire uses a Likert scale with the categories